Three-dimensional covalent organic framework single crystal material of acs topology and preparation method of three-dimensional covalent organic framework single crystal material
Through the synthesis of Schiff base reaction of aldehyde group and aminotriphenylene, a three-dimensional covalent organic frame single crystal material with an ACS topology is formed, which solves the problem of morphology control of covalent organic frame single crystal material, and achieves high crystallinity and rapid dyeing Adsorption improves the thermal stability and adsorption efficiency of the material.
Patent Information
- Application Number
- CN202411445487.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2024-12-24
AI Technical Summary
The preparation of existing covalent organic frame single crystal materials is difficult to control their morphology, resulting in poor crystallinity, insufficient thermal stability and low dye adsorption rate.
2,3,6,7,14,15-hexa(3'-fluoro-4'-formylphenyl)triphenyl and 2,3,6,7,14,15 -hexa(4'-amino-2'-fluorophenyl)triphenylene is used to condense the three-dimensional covalent organic frame single crystal material to form an ACS topology by regulating the amount of aniline.
High crystallinity, permanent porosity and good thermal stability were achieved, and single crystals with complex regular morphology were obtained, and single crystals with the smallest aspect ratio showed a faster dye adsorption rate.
Smart Images

Figure CN119176923A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation of covalent organic framework materials, and specifically relates to an ACS topological three-dimensional covalent organic framework single crystal material and a preparation method thereof. Background Art
[0002] In recent years, crystal morphology control has gained increasing attention by optimizing material properties by simply adjusting the crystal morphology without changing the chemical composition. This performance enhancement method is widely used in various types of crystalline materials, such as semiconductor quantum dots, metals and metal oxides, and gold and silver nanoparticles. In particular, metal organic frameworks (MOFs) have attracted much attention due to their tunable crystal morphology, which has a significant impact on gas storage and separation, dye adsorption, heterogeneous catalysis and fuel cells. As a new type of crystalline porous material, covalent organic frameworks (COFs) have relatively few reports on single crystal growth and crystal morphology control. Most COFs are connected by strong covalent bonds, resulting in poor reversibility, which increases the difficulty of single crystal preparation. In addition, most of the crystals obtained so far lack regular morphology, and the boundaries and facets are not clear, which makes it challenging to precisely control the morphology of COF single crystals. Summary of the invention
[0003] In order to solve the above-mentioned defects of the three-dimensional covalent organic framework single crystal materials existing in the prior art, the present invention provides a three-dimensional covalent organic framework single crystal material with acs topology and a preparation method thereof. A series of three-dimensional covalent organic framework single crystal materials (JUC-663-X) with acs topology are synthesized by synthesizing aldehyde and amino type 2,3,6,7,14,15-hexa(3'-fluoro-4'-formylphenyl)triptycene and 2,3,6,7,14,15-hexa(4'-amino-2'-fluorophenyl)triptycene, and regulating aniline. The three-dimensional covalent organic framework single crystal material synthesized by the method has high crystallinity, permanent porosity, good thermal stability and high crystallinity. The 3D COF single crystal obtained by the present invention exhibits a complex and regular morphology, clear boundaries and clear facets, and its aspect ratio is regulated by regulating the amount of the modulator aniline, wherein the covalent organic framework single crystal with a smaller aspect ratio exhibits a faster dye adsorption rate.
[0004] The present invention is achieved through the following technical solutions:
[0005] In the first aspect, the present invention provides a three-dimensional covalent organic framework single crystal material of ACS topology, which is a covalent organic framework formed by condensation of 2,3,6,7,14,15-hexa(3'-fluoro-4'-formylphenyl)triptycene triangular prism six-connected aldehyde building units and 2,3,6,7,14,15-hexa(4'-amino-2'-fluorophenyl)triptycene triangular prism six-connected amino units through Schiff base reaction, and its structural formula is as follows:
[0006]
[0007] JUC-663-X.
[0008] Further, the chemical structures of 2,3,6,7,14,15-hexa(3'-fluoro-4'-formylphenyl)triptycene and 2,3,6,7,14,15-hexa(4'-amino-2'-fluorophenyl)triptycene are shown below:
[0009]
[0010] In a second aspect, the present invention provides a method for preparing a three-dimensional covalent organic framework single crystal material with ACS topology, and the specific steps are as follows:
[0011] Dissolve 2,3,6,7,14,15-hexa(3'-fluoro-4'-formylphenyl)triptycene in a first organic solvent, add different equivalents of a modulator and shake well, then add a catalyst and shake well, then add 2,3,6,7,14,15-hexa(4'-amino-2'-fluorophenyl)triptycene dissolved in a second organic solvent, seal and let stand, and then obtain a three-dimensional covalent organic framework single crystal material JUC-663-X.
[0012] Furthermore, the molar ratio of 2,3,6,7,14,15-hexa(4'-amino-2'-fluorophenyl)triptycene to 2,3,6,7,14,15-hexa(3'-fluoro-4'-formylphenyl)triptycene is 1:1.
[0013] Furthermore, the first organic solvent is dioxane, and the molar ratio of the first solvent to 2,3,6,7,14,15-hexa(3'-fluoro-4'-formylphenyl)triptycene is 565:1.
[0014] The modulator is aniline, and the addition amount is 30 equivalents to 135 equivalents;
[0015] The catalyst is glacial acetic acid, and the molar ratio of the catalyst to 2,3,6,7,14,15-hexa(3'-fluoro-4'-formylphenyl)triptycene is 452:1;
[0016] The second organic solvent is dioxane, and the molar ratio of the second organic solvent volume to 2,3,6,7,14,15-hexa(3'-fluoro-4'-formylphenyl)triptycene is 1130:1;
[0017] The reaction temperature is 25° C. and the reaction time is 5 days.
[0018] Further, the 2,3,6,7,14,15-hexa(3'-fluoro-4'-formylphenyl)triptycene is prepared by the following method, specifically comprising:
[0019] At 100° C., 2,3,6,7,14,15-hexabromotriptycene, 3-fluoro-4-formylphenylboronic acid, tetrakis(triphenylphosphine)palladium and cesium carbonate are reacted in a mixture of dioxane and water. After the reaction, the solvent is removed under reduced pressure, dichloromethane is added to dissolve the product, and then the product is washed with saturated sodium bicarbonate, deionized water and saturated brine respectively. The organic phase is dried over anhydrous magnesium sulfate and filtered. The solvent is removed by rotary evaporation under reduced pressure to obtain a crude product. The crude product is purified by silica gel (dichloromethane / methanol, 95:1-100:1, v / v) column chromatography to obtain 2,3,6,7,14,15-hexa(3'-fluoro-4'-formylphenyl)triptycene.
[0020] Furthermore, the molar ratio of the 2,3,6,7,14,15-hexabromotriptycene, 3-fluoro-4-formylphenylboronic acid, tetrakis(triphenylphosphine)palladium and cesium carbonate is 2:15-17:0.2:15-17.
[0021] Furthermore, the dioxane / water ratio is (80 mL / 8 mL) when 0.5 g of 2,3,6,7,14,15-hexabromotriptycene is used; the mixture is stirred at 100° C. for 3 days.
[0022] Further, the 2,3,6,7,14,15-hexa(4'-amino-2'-fluorophenyl)triptycene is prepared by the following method, specifically comprising:
[0023] At 100° C., 2,3,6,7,14,15-hexabromotriptycene, 4-amino-2-fluorophenylboronic acid pinacol ester, tetrakis(triphenylphosphine)palladium and cesium carbonate are reacted in dioxane / water. After the reaction, the solvent is removed under reduced pressure, ethyl acetate is added to dissolve the product, and then the product is washed with saturated sodium bicarbonate, deionized water and saturated brine respectively. The organic phase is dried over anhydrous magnesium sulfate and filtered. The solvent is removed by rotary evaporation under reduced pressure to obtain a crude product. The crude product is purified by silica gel (ethyl acetate / n-hexane, 2:1-3:1, v / v) column chromatography to obtain 2,3,6,7,14,15-hexa(4'-amino-2'-fluorophenyl)triptycene.
[0024] Furthermore, the molar ratio of the 2,3,6,7,14,15-hexabromotriptycene, 4-amino-2-fluorophenylboronic acid pinacol ester, tetrakis(triphenylphosphine)palladium and cesium carbonate is 2:15-17:0.2:15-17.
[0025] Furthermore, the dioxane / water ratio is (80 mL / 8 mL) when 0.5 g of 2,3,6,7,14,15-hexabromotriptycene is used; the mixture is stirred at 100° C. for 3 days.
[0026] Compared with the prior art, the advantages of the present invention are as follows:
[0027] 1. The present invention synthesizes 2,3,6,7,14,15-hexa(3'-fluoro-4'-formylphenyl)triptycene and 2,3,6,7,14,15-hexa(4'-amino-2'-fluorophenyl)triptycene for the first time based on 2,3,6,7,14,15-hexabromotriptycene;
[0028] 2. Compared with the previously synthesized covalent organic frameworks, which are mostly small-sized polycrystals with irregular morphology, the present invention synthesizes a series of single crystals with a maximum size of 30 microns using two triangular prism six-connected units for the first time;
[0029] 3. Compared with the three-dimensional covalent organic framework single crystals without clear edges and facets synthesized by using flexible tetrahedral four-connected building units in the past, the present invention uses two rigid triangular prism six-connected building units to synthesize a series of three-dimensional covalent organic framework single crystals with complex regular morphology and clear facets;
[0030] 4. The present invention is the first to obtain single crystals with different aspect ratios by adding different equivalents of the modulator aniline;
[0031] 5. The present invention studies for the first time the effect of single crystals with different aspect ratios on the dye adsorption rate. The single crystal with the smallest aspect ratio has the highest dye adsorption rate. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the following is a brief introduction to the drawings required for the specific embodiments or the description of the prior art. In all the drawings, similar elements or parts are generally identified by similar reference numerals. In the drawings, the elements or parts are not necessarily drawn according to the actual scale.
[0033] Figure 1 The powder X-ray diffraction pattern of JUC-663-X synthesized in the present invention;
[0034] Wherein, a is the experimental powder X-ray diffraction pattern of JUC-663-90, the optimized powder X-ray diffraction pattern and their difference pattern and Bragg position pattern, and b is the PXRD patterns of JUC-663-30 to JUC-663-135;
[0035] Figure 2 This is a scanning electron microscope image of JUC-663-X synthesized by the present invention;
[0036] Among them, a is JUC-663-30, b is JUC-663-45, c is JUC-663-60, d is JUC-663-75, e is JUC-663-90, f is JUC-663-105, g is JUC-663-120, and h is JUC-663-135;
[0037] Figure 3 This is a transmission electron microscope image of JUC-663-X synthesized by the present invention;
[0038] Among them, a is JUC-663-30, b is JUC-663-45, c is JUC-663-60, d is JUC-663-75, e is JUC-663-90, f is JUC-663-105, g is JUC-663-120, and h is JUC-663-135;
[0039] Figure 4 This is an optical microscope image of JUC-663-X synthesized by the present invention;
[0040] Among them, a is JUC-663-30, b is JUC-663-45, c is JUC-663-60, d is JUC-663-75, e is JUC-663-90, f is JUC-663-105, g is JUC-663-120, and h is JUC-663-135;
[0041] Figure 5 Fourier transform infrared spectra of JUC-663-X synthesized by the present invention and raw material monomers;
[0042] Among them, a is the Fourier transform infrared spectra of JUC-663-30 and raw material monomers, b is the Fourier transform infrared spectra of JUC-663-30 to JUC-663-75, and c is the Fourier transform infrared spectra of JUC-663-90 to JUC-663-135;
[0043] Figure 6 This is the thermogravimetric analysis diagram of JUC-663-X synthesized by the present invention;
[0044] Among them, a is the thermogravimetric analysis diagram of JUC-663-30 to JUC-663-75, and b is the thermogravimetric analysis diagram of JUC-663-90 to JUC-663-135;
[0045] Figure 7 This is the N2 adsorption diagram of JUC-663-X synthesized by the present invention;
[0046] Among them, a is JUC-663-30, b is JUC-663-45, c is JUC-663-60, d is JUC-663-75, e is JUC-663-90, f is JUC-663-105, g is JUC-663-120, and h is JUC-663-135;
[0047] Figure 8 This is the pore size diagram of JUC-663-X synthesized by the present invention;
[0048] Among them, a is JUC-663-30, b is JUC-663-45, c is JUC-663-60, d is JUC-663-75, e is JUC-663-90, f is JUC-663-105, g is JUC-663-120, and h is JUC-663-135;
[0049] Fig. 9 This is a comparison chart of the UV absorption spectrum and removal efficiency of JUC-663-45,90,135 synthesized by the present invention when it adsorbs 20 ml of 10 mg / L Rhodamine B within 60 minutes;
[0050] Among them, a is the UV absorption spectrum of JUC-663-45 adsorbing 20 ml of 10 mg / L Rhodamine B within 60 minutes, b is the UV absorption spectrum of JUC-663-90 adsorbing 20 ml of 10 mg / L Rhodamine B within 60 minutes, c is the UV absorption spectrum of JUC-663-135 adsorbing 20 ml of 10 mg / L Rhodamine B within 60 minutes, d is the removal efficiency comparison chart of JUC-663-45, 90, 135 adsorbing 20 ml of 10 mg / L Rhodamine B within 60 minutes;
[0051] Fig.10 This is a comparison chart of the UV absorption spectrum and removal efficiency of JUC-663-45,90,135 synthesized by the present invention when it adsorbs 20 ml of 20 mg / L Rhodamine B within 60 minutes;
[0052] Among them, a is the UV absorption spectrum of 20 ml of 20 mg / L Rhodamine B adsorbed by JUC-663-45 within 60 minutes, b is the UV absorption spectrum of 20 ml of 20 mg / L Rhodamine B adsorbed by JUC-663-90 within 60 minutes, c is the UV absorption spectrum of 20 ml of 20 mg / L Rhodamine B adsorbed by JUC-663-135 within 60 minutes, d is the removal efficiency comparison chart of 20 ml of 20 mg / L Rhodamine B adsorbed by JUC-663-45, 90, 135 within 60 minutes;
[0053] Fig.11This is the UV absorption spectrum and removal efficiency comparison diagram of JUC-663-45,90,135 synthesized by the present invention adsorbing 20 ml of 30 mg / L rhodamine B within 60 minutes;
[0054] Among them, a is the UV absorption spectrum of 20 ml of 30 mg / L Rhodamine B adsorbed by JUC-663-45 within 60 minutes, b is the UV absorption spectrum of 20 ml of 30 mg / L Rhodamine B adsorbed by JUC-663-90 within 60 minutes, c is the UV absorption spectrum of 20 ml of 30 mg / L Rhodamine B adsorbed by JUC-663-135 within 60 minutes, d is the removal efficiency comparison chart of 20 ml of 30 mg / L Rhodamine B adsorbed by JUC-663-45, 90, 135 within 60 minutes;
[0055] Fig.12 The UV absorption spectrum and removal efficiency comparison diagram of JUC-663-45,90,135 synthesized by the present invention adsorbing 20 ml of 10 mg / L rhodamine 6G within 60 minutes;
[0056] Among them, a is the UV absorption spectrum of 20 ml of 10 mg / L Rhodamine 6G adsorbed by JUC-663-45 within 60 minutes, b is the UV absorption spectrum of 20 ml of 10 mg / L Rhodamine 6G adsorbed by JUC-663-90 within 60 minutes, c is the UV absorption spectrum of 20 ml of 10 mg / L Rhodamine 6G adsorbed by JUC-663-135 within 60 minutes, d is the removal efficiency comparison chart of 20 ml of 10 mg / L Rhodamine 6G adsorbed by JUC-663-45, 90, 135 within 60 minutes;
[0057] Fig.13 This is a comparison chart of the UV absorption spectrum and removal efficiency of JUC-663-45,90,135 synthesized by the present invention when it adsorbs 20 ml of 10 mg / L methylene blue within 60 minutes;
[0058] Among them, a is the UV absorption spectrum of JUC-663-45 adsorbing 20 ml of 10 mg / L methylene blue within 60 minutes, b is the UV absorption spectrum of JUC-663-90 adsorbing 20 ml of 10 mg / L methylene blue within 60 minutes, c is the UV absorption spectrum of JUC-663-135 adsorbing 20 ml of 10 mg / L methylene blue within 60 minutes, and d is the removal efficiency comparison chart of JUC-663-45, 90, and 135 adsorbing 20 ml of 10 mg / L methylene blue within 60 minutes. DETAILED DESCRIPTION
[0059] In order to clearly and completely describe the technical solution and its specific working process of the present invention, the specific implementation methods of the present invention are as follows in conjunction with the accompanying drawings of the specification:
[0060] Example 1
[0061] An ACS topological three-dimensional covalent organic framework single crystal material, an organic framework structure formed by condensation of aldehyde-type 2,3,6,7,14,15-hexa(3'-fluoro-4'-formylphenyl)triptycene triangular prism hexalinked building units and amino-type 2,3,6,7,14,15-hexa(4'-amino-2'-fluorophenyl)triptycene triangular prism hexalinked units through a Schiff base reaction, and its structural formula is as follows:
[0062]
[0063] JUC-663-X
[0064] The chemical structural formulas of the 2,3,6,7,14,15-hexa(3'-fluoro-4'-formylphenyl)triptycene and the 2,3,6,7,14,15-hexa(4'-amino-2'-fluorophenyl)triptycene are as follows:
[0065]
[0066] The synthesis process of 2,3,6,7,14,15-hexa(3'-fluoro-4'-formylphenyl)triptycene is as follows:
[0067]
[0068] 2,3,6,7,14,15-hexabromotriptycene (0.5 g, 0.69 mmol), 3-fluoro-4-formylphenylboronic acid (1.5 g, 8.9 mmol), tetrakis(triphenylphosphine)palladium (0.24 g, 0.2 mmol), and cesium carbonate (2.9 g, 8.9 mmol) were reacted in dioxane / water. After the reaction was completed, the solvent was removed under reduced pressure, and dichloromethane was added to dissolve the product. The product was then washed with saturated sodium bicarbonate, deionized water, and saturated brine, respectively. The organic phase was dried over anhydrous magnesium sulfate and filtered. The solvent was removed by rotary evaporation under reduced pressure to obtain a crude product. The crude product was purified by silica gel (dichloromethane / methanol, 95:1-100:1, v / v) column chromatography to obtain 2,3,6,7,14,15-hexa(3'-fluoro-4'-formylphenyl)triptycene as a white powder with a yield of 70%.
[0069] The synthesis process of the 2,3,6,7,14,15-hexa(3'-fluoro-4'-formylphenyl)triptycene is as follows:
[0070]
[0071] 2,3,6,7,14,15-hexabromotriptycene (0.5 g, 0.69 mmol), 4-amino-2-fluorophenylboronic acid pinacol ester (2.11 g, 8.9 mmol), tetrakis(triphenylphosphine)palladium (0.24 g, 0.2 mmol), and cesium carbonate (2.9 g, 8.9 mmol) were reacted in dioxane / water. After the reaction was completed, the solvent was removed under reduced pressure, and ethyl acetate was added to dissolve the product. The product was then washed with saturated sodium bicarbonate, deionized water, and saturated brine, respectively. The organic phase was dried over anhydrous magnesium sulfate and filtered. The solvent was removed by rotary evaporation under reduced pressure to obtain a crude product. The crude product was purified by silica gel (ethyl acetate / n-hexane, 2:1-3:1, v / v) column chromatography to obtain 2,3,6,7,14,15-hexa(3'-fluoro-4'-formylphenyl)triptycene as a light yellow powder with a yield of 65%.
[0072] Example 2
[0073] This embodiment provides a method for preparing a three-dimensional covalent organic framework single crystal material JUC-663-X with acs topology, and the specific steps are as follows:
[0074] Dissolve 2,3,6,7,14,15-hexa(3'-fluoro-4'-formylphenyl)triptylene (HFFPTP, 9.83 mg) in 0.5 ml of dioxane and place in a glass vial. Then slowly add different equivalents (30 equivalents to 135 equivalents) of the modulator aniline and 0.4 ml of glacial acetic acid. Then add 9.18 mg of 2,3,6,7,14,15-hexa(3'-fluoro-4'-formylphenyl)triptylene dissolved in 1 ml of dioxane to the glass vial and shake well. Finally, place it on the table at room temperature for 5 days. After the reaction is completed, open the glass vial, immerse the obtained crystals in anhydrous dioxane, and exchange the solvent with fresh dioxane several times. The sample was then transferred to a vacuum oven, and the solid product was placed in a vacuum oven at 65°C and dried for 3 hours to obtain a yellow (JUC-663-X) target product with a yield of 75% (JUC-663-X). The reaction formula is shown below;
[0075]
[0076] like Figure 1 As shown, through the powder X-ray diffraction spectrum of Rietveld refinement and the powder X-ray diffraction spectrum of JUC-663-X synthesized by the present invention, it can be determined that a series of three-dimensional covalent organic framework single crystal materials with acs topology are successfully synthesized by the method of the present invention;
[0077] like Figure 2As shown, scanning electron microscopy of a series of JUC-663-X single crystals shows the formation of single crystals with regular morphology and clear facets; and the size and aspect ratio of the single crystals increase with the increase of the modulator aniline equivalent.
[0078] like Figure 3 As shown, transmission electron microscopy of a series of JUC-663-X single crystals also shows the formation of single crystals with regular morphology and clear facets; and the size and aspect ratio of the single crystals increase with the increase of the modulator aniline equivalent.
[0079] like Figure 4 As shown, optical microscopy of a series of JUC-663-X single crystals also shows the formation of single crystals with regular morphology and clear facets; and the size and aspect ratio of the single crystals increase with the increase of the modulator aniline equivalent.
[0080] like Figure 5 As shown, by comparing the Fourier transform infrared spectra of the two monomers (HFFPTP and HAFPTP) and the JUC-663-X synthesized by the present invention, the HAFPTP -1 、3480cm -1 The absorption peaks of -NH2 and HFFPTP are at 1690 cm -1 The absorption peak of -CHO disappears, while the absorption peak of JUC-663-X at 1622cm -1 The appearance of the infrared absorption peak of -C=N proves the formation of imine bond.
[0081] like Figure 6 As shown in the figure, JUC-663-X material does not begin to lose weight significantly until about 450°C, indicating that JUC-663-X can withstand high temperatures of 450°C.
[0082] like Figure 7 and Figure 8 As shown in Figure 2, the N2 adsorption of JUC-663-X proves that the specific surface area reaches 2500-2700m 2 g -1 The pore sizes are micropores and mesopores, mainly distributed around 1.0, 1.5 and 2.3 nm.
[0083] like Fig. 9 As shown, the dye adsorption experiment of JUC-663-45, 90, and 135 in 20 ml of an aqueous solution of 10 mg / L Rhodamine B was performed. Among them, the single crystal JUC-663-45 with a smaller aspect ratio has a higher adsorption efficiency. At a lower Rhodamine B concentration, the three JUC-663-Xs can achieve an adsorption rate close to 100% within 60 minutes.
[0084] like Fig.10As shown in the figure, the dye adsorption experiment of JUC-663-45, 90, and 135 in 20 ml of an aqueous solution of 20 mg / L Rhodamine B, in which the single crystal JUC-663-45 with a smaller aspect ratio has a higher adsorption efficiency. At a medium Rhodamine B concentration, JUC-663-45 and JUC-663-90 can reach an adsorption rate of nearly 100% within 60 minutes, while JUC-663-135 can only reach an adsorption rate of 75% within 60 minutes.
[0085] like Fig.11 As shown in the figure, the dye adsorption experiment of JUC-663-45, 90, and 135 in 20 ml of an aqueous solution of 30 mg / L Rhodamine B, in which the single crystal JUC-663-45 with a smaller aspect ratio has a higher adsorption efficiency. At a higher Rhodamine B concentration, JUC-663-45 and JUC-663-90 can reach an adsorption rate of nearly 100% within 60 minutes, while JUC-663-135 can only reach an adsorption rate of 68% within 60 minutes.
[0086] like Fig.12 As shown, in the dye adsorption experiment of JUC-663-45, 90, and 135 in 20 ml of an aqueous solution of 10 mg / L rhodamine 6G, the single crystal JUC-663-45 with a smaller aspect ratio has a higher adsorption efficiency, and their adsorption rates in 60 minutes are 60%, 52%, and 38%, respectively.
[0087] like Fig.13 As shown, in the dye adsorption experiment of JUC-663-45, 90, and 135 in a 20 ml aqueous solution of methylene blue with a concentration of 10 mg / L and a smaller molecular size, the single crystals of three different aspect ratios have similar high adsorption rates, among which the single crystal JUC-663-45 with a smaller aspect ratio has a higher adsorption efficiency, and their 60-minute adsorption rates are 89%, 85%, and 78%, respectively.
[0088] The preferred embodiments of the present invention are described in detail above in conjunction with the accompanying drawings. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0089] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0090] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A three-dimensional covalent organic framework single crystal material with acs topology, characterized in that: It is a covalent organic framework formed by condensation of 2,3,6,7,14,15-hexa(3'-fluoro-4'-formylphenyl)triptycene triangular prism six-linked aldehyde building units and 2,3,6,7,14,15-hexa(4'-amino-2'-fluorophenyl)triptycene triangular prism six-linked amino units through Schiff base reaction. Its structural formula is as follows: JUC-663-X.
2. The acs topological three-dimensional covalent organic framework single crystal material according to claim 1, characterized in that: The chemical structures of 2,3,6,7,14,15-hexa(3'-fluoro-4'-formylphenyl)triptycene and 2,3,6,7,14,15-hexa(4'-amino-2'-fluorophenyl)triptycene are shown below:
3. The method for preparing a three-dimensional covalent organic framework single crystal material with ACS topology according to claim 1, characterized in that: The specific steps are as follows: Dissolve 2,3,6,7,14,15-hexa(3'-fluoro-4'-formylphenyl)triptycene in a first organic solvent, add different equivalents of a modulator and shake well, then add a catalyst and shake well, then add 2,3,6,7,14,15-hexa(4'-amino-2'-fluorophenyl)triptycene dissolved in a second organic solvent, seal and let stand, and then obtain a three-dimensional covalent organic framework single crystal material JUC-663-X.
4. The method for preparing a three-dimensional covalent organic framework single crystal material with ACS topology according to claim 3, characterized in that: The molar ratio of 2,3,6,7,14,15-hexa(4'-amino-2'-fluorophenyl)triptycene to 2,3,6,7,14,15-hexa(3'-fluoro-4'-formylphenyl)triptycene is 1:
1.
5. The method for preparing a three-dimensional covalent organic framework single crystal material with ACS topology as claimed in claim 3, characterized in that: The first organic solvent is dioxane, and the molar ratio of the first solvent to 2,3,6,7,14,15-hexa(3'-fluoro-4'-formylphenyl)triptycene is 565:1; The modulator is aniline, and the addition amount is 30 equivalents to 135 equivalents; The catalyst is glacial acetic acid, and the molar ratio of the catalyst to 2,3,6,7,14,15-hexa(3'-fluoro-4'-formylphenyl)triptycene is 452:1; The second organic solvent is dioxane, and the molar ratio of the second organic solvent volume to 2,3,6,7,14,15-hexa(3'-fluoro-4'-formylphenyl)triptycene is 1130:1; The reaction temperature is 25° C. and the reaction time is 5 days.
6. The method for preparing a three-dimensional covalent organic framework single crystal material with ACS topology as claimed in claim 3, characterized in that: The 2,3,6,7,14,15-hexa(3'-fluoro-4'-formylphenyl)triptycene is prepared by the following method, which specifically includes: At 100° C., 2,3,6,7,14,15-hexabromotriptycene, 3-fluoro-4-formylphenylboronic acid, tetrakis(triphenylphosphine)palladium and cesium carbonate are reacted in a mixture of dioxane and water. After the reaction, the solvent is removed under reduced pressure, dichloromethane is added to dissolve the product, and then the product is washed with saturated sodium bicarbonate, deionized water and saturated brine respectively. The organic phase is dried over anhydrous magnesium sulfate and filtered. The solvent is removed by rotary evaporation under reduced pressure to obtain a crude product. The crude product is purified by silica gel (dichloromethane / methanol, 95:1-100:1, v / v) column chromatography to obtain 2,3,6,7,14,15-hexa(3'-fluoro-4'-formylphenyl)triptycene.
7. The method for preparing a three-dimensional covalent organic framework single crystal material with ACS topology according to claim 6, characterized in that: The molar ratio of the 2,3,6,7,14,15-hexabromotriptycene, 3-fluoro-4-formylphenylboronic acid, tetrakis(triphenylphosphine)palladium and cesium carbonate is 2:15-17:0.2:15-17.
8. The method for preparing a three-dimensional covalent organic framework single crystal material with ACS topology as claimed in claim 3, characterized in that: The ratio of dioxane / water to 2,3,6,7,14,15-hexabromotriptycene (0.5 g) is (80 mL / 8 mL); stir at 100°C for 3 days.
9. The method for preparing a three-dimensional covalent organic framework single crystal material with ACS topology according to claim 3, characterized in that: The 2,3,6,7,14,15-hexa(4'-amino-2'-fluorophenyl)triptycene is prepared by the following method, which specifically includes: At 100° C., 2,3,6,7,14,15-hexabromotriptycene, 4-amino-2-fluorophenylboronic acid pinacol ester, tetrakis(triphenylphosphine)palladium and cesium carbonate are reacted in dioxane / water. After the reaction, the solvent is removed under reduced pressure, ethyl acetate is added to dissolve the product, and then the product is washed with saturated sodium bicarbonate, deionized water and saturated brine respectively. The organic phase is dried over anhydrous magnesium sulfate and filtered. The solvent is removed by rotary evaporation under reduced pressure to obtain a crude product. The crude product is purified by silica gel (ethyl acetate / n-hexane, 2:1-3:1, v / v) column chromatography to obtain 2,3,6,7,14,15-hexa(4'-amino-2'-fluorophenyl)triptycene.
10. The method for preparing a three-dimensional covalent organic framework single crystal material with acs topology according to claim 9, characterized in that: The molar ratio of the 2,3,6,7,14,15-hexabromotriptycene, 4-amino-2-fluorophenylboronic acid pinacol ester, tetrakis(triphenylphosphine)palladium and cesium carbonate is 2:15-17:0.2:15-17; the dioxane / water is (80 mL / 8 mL) when 0.5 g of 2,3,6,7,14,15-hexabromotriptycene is used; and the mixture is stirred at 100° C. for 3 days.
Citation Information
Cited By
A nitrogen-containing heterocycle-linked covalent organic framework material, and a preparation method and application thereof
CN122810349A
